Human Bisphenol A Exposure and the “Diabesity Phenotype” - Simona Bertoli; Alessandro Leone; Alberto Battezzati (Dose-Response, 2015)
Bisphenol A (BPA), a known endocrine disruptor, is a food contaminant suspected of being a contributing factor to the present-day increase in obesity, diabetes, and cardiovascular disease. This issue is of increasing interest in the field of diabetes research and has become a matter of concern for regulatory agencies and food industries. Recently, the number of studies involving BPA has increased exponentially, but there are still many gaps in the knowledge of the relationship between actual BPA exposure and cardiometabolic risk and of the modalities of food intake exposure, all of which prevents sound judgments concerning the risks to human health. This review focuses on the association between human exposure to BPA and obesity, thyroid function, diabetes, insulin resistance, metabolic syndrome, cardiovascular diseases, and BPA content in food. Many cross-sectional studies support, sometimes contradictorily, an adverse effect of BPA exposure on obesity, diabetes, and cardiovascular diseases. Few prospective studies support an adverse effect of BPA exposure on such pathologies. Moreover, no intervention studies have been conducted to evaluate the causality of such associations. This is mainly due to lack of an appropriate database of BPA content in foods, thus hindering any estimation of the usual dietary BPA intake.